"Everything on earth is in a state of constant flux" (55): The Roles of Imagination and Society in Pursuing Lasting Happiness (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2021)
Rousseau's discussion of imagination is interpreted as the key to lasting happiness, both in his Reveriesand in life. Through delving deep into literary devices and the themes of emotional stability, society, and individualism, this essay attempts to shed light on how one can attain a peaceful and fulfilling state of happiness through the use of imagination.For additional context, listen to the author's reflection on the piece below.